EHMT2/G9a Inhibits Aortic Smooth Muscle Cell Death by Suppressing Autophagy Activation - Chen, Tai-Qiang (Int J Biol Sci, 2020)
Although EHMT2 (also known as G9a) plays a critical role in several kinds of cancers and cardiac remodeling, its function in vascular smooth muscle cells (VSMCs) remains unknown. In the present study, we revealed a novel function of EHMT2 in regulating autophagic cell death (ACD) of VSMC. Inhibition of EHMT2 by BIX01294 or knockdown of EHMT2 resulted in reduced VSMC numbers which were independent of proliferation and apoptosis. Interestingly, EHMT2 protein levels were significantly decreased in VSMCs treated with autophagic inducers. Moreover, more autophagic vacuoles and accumulated LC3II were detected in VSMCs treated with BIX01294 or lenti-shEHMT2 than their counterparts. Furthermore, we found that EHMT2 inhibited the ACD of VSMCs by suppressing autophagosome formation. Mechanistically, the pro-autophagic effect elicited by EHMT2 inhibition was associated with SQSTM1 and BECN1 overexpression. Moreover, these detrimental effects were largely nullified by SQSTM1 or BECN1 knockdown. More importantly, similar results were observed in primary human aortic VSMCs. Overall, these findings suggest that EHMT2 functions as a crucial negative regulator of ACD via decreasing SQSTM1 or BECN1 expression and that EHMT2 could be a potent therapeutic target for cardiovascular diseases (e.g., aortic dissection).